Two Cases of Pachydermodactyly Presenting as Polyarthritis - Roxana Mititelu; Sarah Finch; Paul Dancey; Ian Landells (Case Reports in Dermatological Medicine)
Pachydermodactyly is characterized by asymptomatic, progressive swelling of the lateral aspects of the 2nd to 4th finger along the proximal interphalangeal (PIP) joint without involving the joint itself. We present 2 interesting cases of patients with periarticular swelling who were initially diagnosed and treated as juvenile idiopathic arthritis (JIA) with subsequent clinical and pathology confirmation of pachydermodactyly. These cases emphasize the importance of considering pachydermodactyly in young patients with development of periarticular swelling and no joint involvement.